Instagram Social Media Management Strategy @Disparbudpora_Bondowoso As A Communication Medium In Promoting Bondowoso District Tourism - Malaihollo, Trifena Putri (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
This research is motivated by the concern of the Bondowoso Regency Government about falling behind Banyuwangi Regency in promoting one of their top tourist attractions, the Ijen Crater. The Ijen Crater has been recognized as part of the Global Geopark. Currently, many local and foreign tourists consider the Ijen Crater a Banyuwangi tourist destination because it spans two regions. The objectives of this research are first to understand the social media management by the @pariwisata_bondowoso account, and second to assess the impact and results of social media management in promoting tourism in Bondowoso Regency. This research employs a qualitative method. Data Data were collected using observation techniques, direct interviews, and documentation. The conclusion drawn is that the tourism promotion strategy implemented by Disparbudpora is quite good in providing informative and engaging content, but there are challenges in conducting evaluations, which have not been optimal. The impact of Disparbudpora Bondowoso's social media management in promoting tourism in Bondowoso Regency is evident from the followers' responses in the comment section, likes, and the reach achieved by the @pariwisata_bondowoso Instagram account. The result of the social media management by Disparbudpora is that followers receive relevant and high-quality information.